The new Atheisms: a theological-philosophical approach - Amengual Coll, Gabriel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The author offers a panoramic vision of to-day’s main forms of atheism with the purpose to widen the view beyond the so-called «new atheisms». In order to emphasize details, they are divided into two kinds: soft atheisms, generally proceeding from nihilism, and militant, hard atheisms, whose arguments are posited on behalf of science. Among the first, the author mentions the masters: Heidegger and Wittgenstein, and then their more important exponents, like Derrida, Vattimo and Rorty, as well as some philosophers/sociologists (Lübbe, Habermas and Beck). Among the hard atheisms, the author differentiates those who argue from biology (Dawkins and Dennett) from those who do it from culture (Assmann and Sloterdijk). But before either, you will find a mention of Nietzsche, who really inspires all new atheisms, save the scientific varieties. The conclusion includes some thoughts about the true meaning and scope of these new criticisms of religion.
Keywords: New atheisms; Science and Faith; criticism of the religion; secularization; God’s transcendence; God and Cosmos; God’s kenosis. Nietzsche; Derrida; Vattimo; Rorty; Dawkins; Dennett; Sloterdijk.